KAJIAN POTENSI UNTUK EKOWISATA DI PANTAI LESTARI INDAH KABUPATEN SERDANG BEDAGAI SUMATERA UTARA (Study Potential for Ecotourism in Lestari Indah beach, Serdang Bedagairegency, North Sumatra province ) - Tengku Muhammad Fadrika; Rahmawaty Rahmawaty; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
T. Muhammad Fadrika, Study Potential for Ecotourism in Pantai Indah Lestari,Serdang Bedagai regency , North Sumatra province, under guided Rahmawatiand Zulham Apandy Harahap.Indah Lestari beach has natural resource potential to be a place thatsupports tourism, especially ecotourism ecotourism which in this case is based ona sightseeing trip to keep the coastal environment. Tourism activities shouldinvolve several parties such as visitors, local communities and managers to beable to put to good use.The research was conducted in Lestari Indah beach , Serdang Bedagairegency of North Sumatra Province. This research was conducted from Octoberto November, 2013 by taking the physical parameters of the questionnaire andalso taking part - related parties. Suitability Index Areas, Sustainable CoastalScenic can be used as tourist attractions. Capability Areas can still beaccommodated by the coastal areas, so as not to damage Indah Lestari Coastregion. The best alternative strategy for the development of SustainableEcotourism in Coastal Indaah is to do a good promotion through the internet andprint media.Keywords : Ecoutourism, Carrying Capacity Region And SWOT